中国东北人移民新加坡后的语言变化及其社会意义 = Study of the language changes of Chinese Northeastern immigrants as a socio-linguistic Indicator in Singapore - 李思 Li, Si (2018)
新加坡的华人移民语言研究集中于马来西亚和中国闽粤一带，随着更多来自中国北方的华人移居新加坡，使新加坡的华人群体更加多元化。在这个大前提下，本文从宏观的社会语言学角度，着重探讨从中国东北三省移民至新加坡的这一群体，并与定居在中国的东北人对比，分析移民在语音和语用习惯方面的变化，以及该变化与移民自身和社会的相关性，同时发掘该移民群体的语言态度与新加坡归属感的关系。 本文采取语音测试、问路调查和问卷调查法，对新中两地各20位东北人进行资料收集和测试。调查取样的过程注重全面性，涵盖不同年龄和社会阶层，使研究结果具有代表性。本研究的语音测试通过阅读一则新闻稿和18个词组，再借用PRAAT语音软件，根据共振峰分析新中两地的东北人在舌尖后音、辅音r音和尾韵母o音的发音特点，另外依据音强和音调分别对声调和一声音节进行分析。本研究还通过“问路”的形式调查新中两地的东北人在自然表达时对于动词、名词和语码混用方面的差异。此外，采用问卷形式，了解东北移民的背景、语言态度和社会认同，借以探讨语言变化与其家庭环境、职业、受教育程度、年龄和在新加坡居住时长的相关性，同时分析语言态度与新加坡归属感的关系。 论文的结论是，在脱离中国东北后，同时又受到新加坡多语环境的影响，东北移民在尾韵母o音、声调和一声音节的发音变化较大，在用语习惯方面也展现出偏离东北化，贴近标准化和新加坡化的现象。同时语言变化与东北移民的职业和年龄有密切关系，但与其受教育程度、家庭环境和在新加坡居住时长无关。另外，对新加坡语言持正面语言态度的东北移民能更好的融入新加坡社会，社会归属感更强。 The linguistic studies of Chinese immigrants in Singapore are mainly focuses on Malaysia, Fujian and Guangdong, as more Chinese from northern China immigrate to Singapore in recent years, the Chinese community in Singapore become more diverse. This thesis, from the perspective of macro social linguistics, focus on immigrants from the three northeast provinces of china. It attempts to study the phonetic and lexical changes of these immigrants and to explore the reasons behind it. At the same time, investigate their identity and attribution based on their language attitude about Singapore. This thesis has conducted detailed analysis on 20 Northeastern Chinese living in Singapore and China respectively through phonetic test, questionnaire and social experiment. The phonetic test is conducted by reading a newspaper article and 18 phrases. With the help of the PRAAT phonetic software, the sound on apical consonant, R consonant and final vowel are analysed by their formant shown in PRAAT, tones and first tone syllable are analysed by intensity and pitch respectively. The thesis is also investigated the lexical changes by doing social experiment like “asking the way”. Besides that, it collects data about northeastern immigrants’ personal background, language attitude and social attribution in order to analyse their language changes with reference to 5 different variables such as family background, occupation, education level, age and the length of residence in Singapore. Also, to investigate their identity and attribution based on their language attitude about Singapore. The conclusion of this thesis is that, with the influence of Singapore multilingual environment, the northeastern immigrant’s pronunciation is drastically changed, especially on final vowel, tone and one syllable . In terms of lexical changes, they speak less northeast dialect but more mandarin and their speaking habits are more close to Singaporean. At the same time, immigrant’s occupation and age are the two major factors which affecting their language change. In addition, immigrants who have positive language attitudes towards Singaporean language can better integrate into the society and have a stronger sense of belonging.